Assessing the Correlation Between Basic Sanitation and Diarrhea Prevalence in Bulurejo Village, Gresilk: A Geographic Information System (GIS) Approach - Silvia Retna Ning Tyias; Narwati Narwati; Demes Nurmayanti; Suprijandani; Leila Florento (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
In 2022, the number of diarrhea cases increased to 958 sufferers, with the highest incidence occurring in Bulurejo village. Physically, the sources of clean water still exhibit discoloration and unpleasant odor. The latrine construction lacks a roof, and the walls are made of cloth. The construction of waste bins lacks covers, and the wastewater disposal facilities (SPAL) are open. This research aims to determine the correlation between basic sanitation and the prevalence of diarrhea using the Geographic Information System (GIS) method. The study is descriptive-analytical through observations and a GIS approach in the form of a map. From the observations, bivariate and univariate analyses were conducted using the chi-square test. The results show that basic household sanitation is related to the prevalence of diarrhea in Bulurejo. Clean water facilities, with a p-value of 0.014, indicate a significant relationship. Toilet facilities, with a p-value of 0.347, show no significant relationship. SPAL facilities, with a p-value of 0.009, indicate a significant relationship. Waste disposal facilities, with a p-value of 0.029, indicate a significant relationship. After analysis, the results were represented in the form of a map. The Geographic Information System (GIS) approach was utilized to develop more effective mapping strategies for the improvement of sanitation and diarrhea control in the area. These findings indicate the necessity for enhancing basic sanitation facilities and implementing programs at community health centers to reduce diarrhea cases in Bulurejo.